The Role Of Healthcare Professionals In Shaping Public Health Practice In Saudi Arabia: A Narrative Review (The Review of Diabetic Studies, 2024)
Healthcare professionals are at the heart of public health systems, shaping community well-being through their daily commitment to disease prevention, health promotion, and policy implementation. In Saudi Arabia, the rapid transformation of the health sector—driven by Vision 2030—has put a spotlight on the vital contributions of doctors, nurses, allied health professionals, and community-based practitioners. This review explores their evolving roles, the challenges they encounter, and the innovative strategies being developed to empower them. By understanding these dynamics, we can better support the people behind the progress and pave the way for a healthier future for everyone in the Kingdom.